Substance Abuse among Bipolar Mood Disorder Patients - Rashid, Mohammad Harunur; Ahmed, Ahsan Uddin; Khan, Muhammad Zillur Rahman (Delta Medical College Journal, 2019)
Background: Substance abuse is a major comorbidity among patients with bipolar mood disorder (BMD). In a major portion of patients with BMD substance abuse remains undiagnosed and untreated in Bangladesh. Objective: This descriptive cross sectional study was conducted from November, 2014 to May, 2015 to determine proportion of substance abuse among patients with BMD. Materials and method: A total of 151 patients with bipolar mood disorder were selected purposefully from both the inpatient and outpatient department of National Institute of Mental Health (NIMH), Dhaka, Bangladesh. Both male and female were included and informed written consent was taken from each respondent. During data collection, a structured questionnaire designed by the researchers containing socio-demographic and other variables was used. Results: Among the respondents 23.8% was found to abuse substance. Conclusion: So during the treatment of BMD the physicians should always search for substance abuse among the patients and treat them accordingly to achieve a fruitful outcome. Delta Med Col J. Jan 2019 7(1): 31-34